Community College Teachers’ Perceptions and Practices of ICT Integrated Teaching (Journal of Bhuwanishankar, 2022)
In the present pedagogical context of higher education in Nepal, Information and Communication Technology (ICT) integration in classroom pedagogy has become an evolving phenomenon. The community college teachers of Chitwan district are gradually shifting to technology-enhanced classroom pedagogy from the conventional mode of instruction for better teaching and learning outcomes. Although the stakeholders have emphasized ICT integrated pedagogy, teachers have experienced several barriers to its effective integration in the regular classroom activities. In this context, the present study examined community college teachers' perceptions and practices of integrating ICT in the community colleges in Chitwan, the perceived barriers to its effective integration, and ways of overcoming such barriers. The study was carried out employing a quantitative research approach and survey design. The researcher used the Convenience Sampling Method to purposively collect responses from forty teachers from nine community colleges teaching at bachelor’s and master’s levels. The data collected through the questionnaire were analyzed using percentage and frequency distribution statistical tools. The analysis of responses revealed that the status of ICT integration in the classroom did not seem satisfactory, although the teachers had positive perceptions of technology-supported teaching. The perceived major barriers were lack of enough ICT-friendly infrastructures and resources, insufficient ICT-based professional development opportunities, and the lack of students’ digital literacy. The findings of the research imply that community colleges and faculties need more ICT-based teacher development programs, well-equipped ICT infrastructure, budgetary support, increased digital competence and accessibility of students, and an inculcation of ICT-based pedagogical culture to enhance its effectiveness for better teaching-learning outcomes.